Analisis Kelayakan Usaha Budidaya Pembesaran Ikan Lele Di Kota Denpasar Dari Kriteria Undiscounted - Mahayanthi, I Gusti Ayu Dewi; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The purpose of this study was to determine the feasibility of the enlargement of catfish farming in Denpasar based on the data analysis of undiscounted criteria which are Payback Period and Break Even Point (BEP). This research was conducted in Denpasar City. The amount samples taken was 56 catfish farmers, using the formula Slovin. Data collected through interviews, observations, and questionnaires. Based on the analysis it was found that the cultivation of rearing catfish in Denpasar is eligible to run. It is seen from the calculation based on the criteria of investment payback period in 8 months and the results of the break even point on the BEP unit is 216 kg and BEP price is Rp. 3.029.690.00.
Keywords: Keywords: feasibility analysis, catfish, and investment criteria